Low Self-Control and Delinquent Behavior Among Caribbean Youths: The Moderating Role of Parental Supervision - Baek, Hyunin (International journal of offender therapy and comparative criminology, 2025)
Delinquent behavior represents a serious concern in the Caribbean. In order to provide insights useful for explaining deviant behavior among youths in Caribbean countries, this study examines the importance of self-control and parental supervision as predictors of deviant behavior. The study assesses direct as well as interaction effects of both variables. For the study, data from Guyana, St. Kitts and Nevis and St. Lucia were analyzed. The sample included 1,140 juveniles aged between 10 and 19 years. The results of regression analyses showed that self-control was a significant predictor of delinquent behavior. It was also found that the provision of parental supervision was able to mitigate the impact of low self-control on delinquency. This finding applied to males as well as females in the sample.